Neodymium isotope ratio measurements by LC-MC-ICPMS for nuclear applications: investigation of isotopic fractionation and mass bias correction. Issue 2 (19th December 2014) - Guéguen, Florence; Isnard, Hélène; Nonell, Anthony; Vio, Laurent; Vercouter, Thomas; Chartier, Frédéric
Abstract : The causes of isotope ratio drifts observed in LC-MC-ICPMS experiments could be explained by both mass dependent isotopic fractionation on the chromatographic column and distinct time lags between amplifier responses of the Faraday cup configuration. Abstract : Accurate measurements of neodymium isotope ratios in irradiated nuclear fuel samples are fundamental for the validation of neutronic calculation codes, in particular for burn-up qualification. To prevent possible spectral and non-spectral interferences, neodymium is generally purified from the complex sample matrices prior to measurements by mass spectrometric techniques. This work describes the on-line coupling of ion exchange chromatography with multi-collector inductively coupled plasma mass spectrometry for Nd isotope ratio measurements. In the first part of the paper, the causes of the isotope ratio drifts traditionally observed during transient signal acquisitions are investigated. Both mass-dependent isotopic fractionation on the chromatographic column and distinct time lags between amplifier responses of the Faraday cup configuration were shown to be the main phenomena involved in the observed isotope ratio drifts. In the second part, we present a new approach for mass bias correction called "Intra Injection Sample-Standard Bracketing (IISSB)" based on direct "on-line" injection of the standard via the chromatographic system before and after the analyte. This new method, particularly adapted to analysis of nuclear materials, was validated by on-line measurements on a simulated sample representative of fission products present in an irradiated uranium material. Reproducibilities obtained by IISSB were found to be comparable with those found in off-line measurements and classical sample-standard bracketing technique for mass bias correction on all Nd isotope ratios.